Evaluasi User Experience Gim Valorant menggunakan Metode Enhanced Cognitive Walkthrough pada Pengguna Baru - Ezar Chrisdinan Diass; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Valorant is a team-based FPS (First-Person Shooter) game released by Riot Games on June 2, 2020. Valorant is very popular on the Twitch platform. User experience is very important in a game. Games that have good user experience will be easier to be accepted by users and can compete in the market. Games need to be evaluated in order to have a good user experience. The Enhanced Cognitive Walkthrough method is a user experience evaluation method where respondents are asked to perform scenario-based tasks that have been prepared by the evaluator using trial and error techniques. Respondents are given 2 types of questions to find usability problems in the game interface. The respondents in this study were 5 people who had never played the game Valorant. The evaluation results showed that in general the interface in the game valorant was very good. The problems found mostly occurred at the level 3 and 4 of problem seriousness so that they are considered as minor problem and easy to handle. The problems found mostly caused by the lack of user experience in playing valorant (User). The main problem that arises and needs to be fixed in valorant found in task number 2: play tutorial. Respondents had difficulty finding function instructions because the instructions did not provide the required information (Hidden). Respondents also had difficulty interpreting the interface due to design flaws such as too small text size and too small setting buttons, as well as confusing placement (Text and Icon).